Asymmetry of (13)C labeled 3-pyruvate affords improved site specific labeling of RNA for NMR spectroscopy - Thakur, Chandar S. (Springer Netherlands, 2011)
Selective isotopic labeling provides an unparalleled window within which to study the structure and dynamics of RNAs by high resolution NMR spectroscopy. Unlike commonly used carbon sources, the asymmetry of (13)C-labeled pyruvate provides selective labeling in both the ribose and base moieties of nucleotides using Escherichia coli variants, that until now were not feasible. Here we show that an E. coli mutant strain that lacks succinate and malate dehydrogenases (DL323) and grown on [3-(13)C]-pyruvate affords ribonucleotides with site specific labeling at C5′ (~95%) and C1′ (~42%) and minimal enrichment elsewhere in the ribose ring. Enrichment is also achieved at purine C2 and C8 (~95%) and pyrimidine C5 (~100%) positions with minimal labeling at pyrimidine C6 and purine C5 positions. These labeling patterns contrast with those obtained with DL323 E. coli grown on [1, 3-(13)C]-glycerol for which the ribose ring is labeled in all but the C4′ carbon position, leading to multiplet splitting of the C1′, C2′ and C3′ carbon atoms. The usefulness of these labeling patterns is demonstrated with a 27-nt RNA fragment derived from the 30S ribosomal subunit. Removal of the strong magnetic coupling within the ribose and base leads to increased sensitivity, substantial simplification of NMR spectra, and more precise and accurate dynamic parameters derived from NMR relaxation measurements. Thus these new labels offer valuable probes for characterizing the structure and dynamics of RNA that were previously limited by the constraint of uniformly labeled nucleotides. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10858-011-9582-5) contains supplementary material, which is available to authorized users.